2004
DOI: 10.1007/s00417-004-0941-8
|View full text |Cite
|
Sign up to set email alerts
|

Group IIA phospholipase A2 content of tears in patients with atopic blepharoconjunctivitis

Abstract: The results indicate that in patients with ABC the GIIAPLA(2) content of tears was decreased, without any dependence on the quantity of different conjunctival cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
(19 reference statements)
0
9
1
1
Order By: Relevance
“…A plausible explanation of the low values of GIIAPLA 2 in tears of patients with ocular rosacea is increased consumption due to longstanding continuous staphylococcal stimulation. However, even this explanation is suitable only to more severe cases of ocular rosacea with dry eye symptoms in the same way as reported in ABC (Peuravuori et al 2004).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A plausible explanation of the low values of GIIAPLA 2 in tears of patients with ocular rosacea is increased consumption due to longstanding continuous staphylococcal stimulation. However, even this explanation is suitable only to more severe cases of ocular rosacea with dry eye symptoms in the same way as reported in ABC (Peuravuori et al 2004).…”
Section: Discussionmentioning
confidence: 89%
“…An earlier study reported slightly but not significantly decreased levels of tear lactoferrin in chronic meibomitis associated with acne rosacea (Kiratli et al 2000). Interestingly, tear GIIAPLA 2 and lysozyme levels are likewise decreased in patients with ABC (Saari & Klockars 1983; Peuravuori et al 2004) and the disorders share clinical features of chronic inflammation of the conjunctiva and lid margin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge no mechanistic study has been carried out to investigate the inflammatory mediator role of sPLA2-IIa on the ocular surface, despite the concentration or activity of sPLA2-IIa in tears being reported significantly changed in patients with external inflammatory diseases, such as dry eye disease (Aho et al, 2002), post PRK laser surgery (Aho et al, 2003), chronic blepharitis (Song et al, 1999), ocular rosacea (Kari et al, 2005) and atopic blepharoconjunctivitis (Peuravuori et al, 2004). These clinical documentations imply that there may be an association of tear sPLA2-IIa with inflammatory diseases of the ocular surface.…”
Section: Introductionmentioning
confidence: 99%
“…Dermatite atópica (DA) é uma doença inflamatória crônica da pele, que ocorre mais comumente entre a infância e a adolescência e resulta em defeitos na barreira de proteção da pele, do sistema imunológico e respostas exacerbadas a antígenos microbianos e alérgenos (1)(2)(3)(4)(5)(6)(7)(8) .…”
Section: Resumo Introduçãounclassified